2011
DOI: 10.1016/j.neuroscience.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Human hypothalamus shows differential responses to basic motivational stimuli—an invasive electrophysiology study

Abstract: Abstract-The hypothalamus supports basic motivational behaviours such as mating and feeding. Recording directly from the posterior inferior hypothalamus in a male patient receiving a deep brain stimulation (DBS) electrode for the alleviation of cluster headache, we tested the hypothalamic response to different classes of motivational stimuli (sexually relevant: pictures of dressed and undressed women; pictures of food) and pictures of common objects as control. Averaged local field potentials (LFP) to sexually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Based on electrophysiological recordings and functional MRI, it has recently been established that the response of the human hypothalamus to stimuli associated with food intake is greatly reduced when the test subjects are satiated [21,22]. Furthermore, animal studies have demonstrated that the ventromedial and lateral hypothalamus are implicated in the regulation of feeding and energy metabolism and therefore considered as possible targets for clinical DBS aimed at treating morbid obesity [1,2,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Based on electrophysiological recordings and functional MRI, it has recently been established that the response of the human hypothalamus to stimuli associated with food intake is greatly reduced when the test subjects are satiated [21,22]. Furthermore, animal studies have demonstrated that the ventromedial and lateral hypothalamus are implicated in the regulation of feeding and energy metabolism and therefore considered as possible targets for clinical DBS aimed at treating morbid obesity [1,2,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…to common control items, however, they did not characterize frequency-band specific results (Nager et al, 2011). Brittain et al (2009) demonstrated that during a CH attack, there was a significant increase in beta-band (20 Hz) field potential power, representing a possible pathologically-relevant biomarker.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, only two studies have reported on field potentials in the posterior hypothalamus. Nager et al (2011) demonstrated event-related field potential differences to motivational (sexually-relevant and food) stimuli compared FIGURE 2 | (A) Initial parameters at 2-weeks post-operation and 1.5-year post-surgically with DBS lead depicting active contacts in green. (B) Regions of interest (ROIs) with greatest tractography-based proportion of streamlines (>5% of normalized streamlines) to the volume of activated tissue (VAT) with parameters at 2-weeks post-operation, and 1.5-years post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is uncertain whether our findings may be extrapolated to other pathological states. In a patient with cluster headache treated with posterior hypothalamic DBS, LFPs have been recorded following the presentation of food images but oscillatory patterns were not studied in detail …”
Section: Discussionmentioning
confidence: 99%